Influence of incubation temperature on chorio-allantoic membrane vascularization heart size and ascites incidence in broilers (Gallus domesticus) - Wandrag, D.B.R. (University of Pretoria, 2018)
Dissertation (MMedVet)--University of Pretoria, 2018.